Cloning of a pig homologue of the human lactoferrin receptor: Expression and localization during intestinal maturation in piglets - Liao, Yalin (2007)
The presence of a small intestinal lactoferrin receptor (SI-LfR) has been suggested in the pig, but remains to be identified. LfR has been suggested to play a key role in the internalization of lactoferrin (Lf) and to facilitate absorption of iron bound to Lf. The aim of this study was to identify the pig SI-LfR cDNA, determine its mRNA and protein expression during different stages of intestinal development. The coding region of the pig LfR cDNA was cloned by PCR using conserved sequences among species. LfR mRNA expression and protein abundance were measured in proximal small intestine from piglets at 1 week (pre-weaning), 3 weeks (weaning) and 6 months (post-weaning) of age by quantitative (real-time) RT-PCR (Q-PCR) and Western blot, respectively. Intestinal brush border membrane vesicles (BBMV) were also isolated to examine LfR abundance on the apical membrane. We determined the pig SI-LfR open reading frame (ORF) consists of 972 bp, resulting in a protein with a molecular mass ~135 kD and ~35 kD under non-reducing and reducing conditions, respectively. Using Q-PCR, we determined LfR expression significantly increased with age in the duodenum and reciprocally decreased in the jejunum. Intestinal LfR protein expression was maintained at all timepoints in the jejunum; however, in the duodenum LfR abundance reached maximum levels at 6 months. In BBMV fractions, LfR abundance significantly increased with age. Taken together our findings demonstrate the presence of a human SI-LfR homologue in pig, with mRNA and protein expression concomitantly regulated in the duodenum and inversely regulated in the jejunum. These findings suggest a mechanism by which pig Lf can be internalized in the intestine.